Vaccine Politics: Comparison of Acceptance of COVID-19 Vaccines Produced by Democratic and Non-Democratic Countries - Habibilla, Akbar Fasya; Fahadayna, Adhi Cahya (Jurnal Politik, 2023)
The unequal distribution of the COVID-19 vaccine worldwide is one of humanity's global challenges due to political factors entering and influencing the distribution of vaccines to countries worldwide. Vaccine-producing countries are fragmented into two sides: democratic and non-democratic countries. This article aims to answer how political factors can influence the distribution of the COVID-19 vaccine globally and which vaccine is the global favorite. This article uses vaccine politics theory as its basis and uses descriptive-comparative methods in the data analysis process. The results of this research found that there were indications that illiberal democratic practices were widespread during the COVID-19 pandemic, followed by the decision of the head of state to regulate the distribution of vaccines in their country, which tended to be authoritarian during the pandemic. Apart from that, vaccines produced by democratic countries are the favorite of the global community compared to vaccines produced by non-democratic countries. The transparency factor in the production process is the primary benchmark in assessing product quality in addition to the country of origin.